Potensi Pengembangan Kawasan TOD dalam Rencana Pembangunan MRT Koridor Timur-Barat : Studi Kasus: Stasiun MRT Grogol - Arsha Riyantikha Meraldha; Mochamad Kahfi Firdaus (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The rapid population growth and urbanization in Jakarta have led to various urban challenges, one of the most significant being traffic congestion, which incurs substantial economic losses. One proposed solution is the development of Transit Oriented Development (TOD) areas, particularly through the expansion of mass transit infrastructure such as the Mass Rapid Transit (MRT) system. This study examines the potential for TOD development in the planned East–West MRT Corridor, with a case study focused on the Grogol MRT Station. This area is considered strategically significant due to its integration with multiple transportation modes, including TransJakarta, microtrans services, and a Type B bus terminal. This research employs a quantitative approach, utilizing both primary and secondary data. The assessment is conducted using a TOD Index method based on three core principles: density, diversity, and design. The analysis reveals that the Grogol MRT Station area has a population density of 19,953 people/km² and a building density of 2,741 units/km², both of which meet the criteria for an urban-scale TOD. The land use entropy index is 0.63, indicating a moderate level of land-use diversity. However, the availability of pedestrian paths (33.96%), bicycle lanes (1.67%), parking facilities (1.84%), and open green space (1.79%) remains significantly below the ideal TOD standards. Overall, the TOD Index score for this area is 0.417, placing it among the bottom five MRT stations in Jakarta. Despite this, the area fulfills the density requirements for urban TOD classification. Nevertheless, challenges remain, including insufficient pedestrian and bicycle infrastructure, limited green spaces, and low land-use diversity. Planning interventions are thus necessary, focusing on the provision of integrated pedestrian and cycling infrastructure, functional public spaces, and mixed-use zoning to promote sustainable urban mobility.